Core-sheath type MOFs (at) TiO2 nanofiber-shaped composite photocatalyst, preparation method and application of core-sheath type MOFs (at) TiO2 nanofiber-shaped composite photocatalyst

By constructing a core-sheath MOFs@TiO2 composite photocatalyst on flexible TiO2 nanofibers, using amino functionalization and Cu nanoparticle modification, the problems of low photocatalytic CO2 reduction efficiency and complex products are solved, and efficient CO2 conversion and selection are achieved The improvement of performance has promoted the development of photocatalytic technology.

CN119140160APending Publication Date: 2024-12-17YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410572643.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing photocatalytic CO2 reduction technology faces the problems of low photocatalytic efficiency and complex products. The preparation process of composite photocatalysts is cumbersome, making it difficult to build a stable contact interface, which limits the development of MOFs in composite photocatalytic systems.

Method used

The core-sheath MOFs@TiO2 composite photocatalyst was constructed on flexible TiO2 nanofibers by layer-by-layer growth (LBL) method. Through amino functionalization and Cu nanoparticle deposition modification, the covalent connection interface and photoelectron trap between MOFs and TiO2 are realized. , improve CO2 capture and conversion efficiency.

Benefits of technology

The efficiency and selectivity of photocatalytic CO2 preparation of CO and C2H5OH are significantly improved, the regulation of photocatalytic activity and selectivity is achieved, and good long-term stability and sustainability are demonstrated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140160A_ABST
    Figure CN119140160A_ABST
Patent Text Reader

Abstract

The invention discloses a core-sheath type MOFs (at) TiO2 nanofiber-shaped composite photocatalyst as well as a preparation method and application of the core-sheath type MOFs (at) TiO2 nanofiber-shaped composite photocatalyst. The preparation method comprises the following steps: by taking a Cu-pre-embedded TiO2 nanofiber as a substrate, growing a metal-organic framework material (MOFs) on the TiO2 nanofiber in an in-situ layer-by-layer growth (LBL) manner to obtain the catalyst HKUST-1 (at) TiO2 with photocatalytic CO2 reduction activity, the Cu / NH2-HKUST-1-coated TiO2 nanofiber-shaped composite photocatalyst with a core-sheath structure is obtained by further adopting amino functional ligand replacement and Cu nanoparticle deposition modification, and the reduction efficiency of photocatalytic CO2 and the selectivity of reduction products can be directionally regulated and controlled. The invention provides a universal and efficient composite photocatalyst and a preparation method thereof for photocatalytic CO2 reduction and precise regulation and control of product selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalysts, and in particular relates to a core-sheath type MOFs@TiO2 photocatalyst and a preparation method and application thereof. Background Art

[0002] The continuous consumption of fossil fuels has led to excessive CO2 emissions, causing severe global environmental and energy crises. Photocatalytic CO2 technology can use unlimited renewable solar energy to convert CO2 into high-value-added chemicals, which is an ideal solution to global energy and environmental problems.

[0003] The existing photocatalytic CO2 reduction technology is mainly faced with problems such as low photocatalytic efficiency and complex products. A single photocatalyst is limited by its energy band structure and function, and it is difficult to show ideal photocatalytic activity. Combining two or more photocatalysts is an ideal choice to synergistically utilize the advantages of different catalysts and improve the photocatalytic activity of CO2. The preparation process of existing composite photocatalysts relies on cumbersome physical and chemical modifications, and the application of the method is limited. It is of great significance to find a new universal composite photocatalyst preparation method. Metal-organic framework materials (MOFs) have a large specific surface area, a stable three-dimensional structure, system-controllable functional sites, and a highly crystallized and controllable growth process. They are ideal choices for constructing composite photocatalysts and solving the problems faced by existing photocatalytic technologies. The biggest challenge in developing MOFs-based composite photocatalytic systems is how to construct a stable contact interface between MOFs and other semiconductors. Only by constructing a close interface with atomic-level contact can efficient photogenerated electron-hole separation be achieved in the composite catalyst system, thereby improving the photocatalytic efficiency and activity. The technologies used by various MOFs composite photocatalysts reported are different and can only be applied to specific systems, which limits the development of MOFs in composite photocatalytic systems. Therefore, developing a universal composite photocatalyst construction method based on MOFs is of great significance for promoting the development of photocatalytic technology, achieving efficient CO2 emission reduction, and realizing carbon peak and carbon neutrality as soon as possible. Summary of the invention

[0004] The present invention provides a universal method for preparing a MOFs@TiO2 composite photocatalyst with a core-sheath structure and application of the MOFs@TiO2 composite photocatalyst in photocatalytic CO2 reduction.

[0005] Core-sheath MOFs@TiO2 is a flexible TiO2 nanofiber core, which is obtained by in-situ growth of a metal-organic framework (MOFs) sheath on the TiO2 surface by LBL. Furthermore, the core is a TiO2 nanofiber pre-embedded with copper;

[0006] Further, the MOFs is HKUST-1, and is modified by amino functionalization and Cu nanoparticle deposition, respectively;

[0007] Furthermore, MOFs were grown on the TiO2 surface by LBL method to construct a core-sheath structure;

[0008] The application of the core-sheath type HKUST-1@nanofiber TiO2 composite photocatalyst in the reduction of CO2 to produce CO.

[0009] The application of the core-sheath type NH2-HKUST-1@nanofiber TiO2 composite photocatalyst in the reduction of CO2 to produce CO.

[0010] The application of the core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst in the reduction of CO2 to produce C2H5OH.

[0011] The core-sheath MOFs@nanofiber TiO2 composite photocatalyst designed by the present invention uses the LBL method to covalently grow HKUST-1 on TiO2 nanofibers in situ, construct a covalent connection interface between MOFs and TiO2, and achieve carrier separation between the interfaces. The amino functionalization of MOFs can further enhance the photocatalyst's ability to capture and adsorb CO2, significantly improving the efficiency and selectivity of photocatalytic CO2 to produce CO; Cu nanoparticle deposition modification provides additional photoelectron traps and carbon-carbon coupling sites, achieving photocatalytic CO2 to produce C2H5OH, and fully realizing the regulation of photocatalytic efficiency and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is the XRD spectrum of the MOFs@TiO2 material series in Example 1 of the present invention.

[0013] Figure 2 This is a scanning electron microscope photograph of the series of MOFs@TiO2 materials in Example 1 of the present invention.

[0014] Figure 3 This is a transmission electron microscope photo of the series of MOFs@TiO2 materials in Example 1 of the present invention.

[0015] Figure 4 This is the XPS spectrum analysis of the series of MOFs@TiO2 materials in Example 1 of the present invention, a) is the 2p energy spectrum of the Cu element, b) is the Auger energy spectrum of the Cu element, and c) is the 1s energy spectrum of the N element.

[0016] Figure 5 This is the CO2 adsorption-desorption isotherm of the MOFs@TiO2 material series at 273K in Example 1 of the present invention.

[0017] Figure 6 This is a comparison chart of the efficiency of the series of MOFs@TiO2 materials in Example 1 of the present invention for reducing CO2 to generate CO and CH4.

[0018] Figure 7 This is a comparison chart of the efficiency of the series of MOFs@TiO2 materials in Example 1 of the present invention for reducing CO2 to produce CH3OH and C2H5OH.

[0019] Figure 8 This is the reproducibility of the photocatalytic CO2 reduction of HKUST-1@TiO2 in Example 1 of the present invention.

[0020] Fig. 9 This is the reproducibility of the photocatalytic CO2 reduction of NH2-HKUST-1@TiO2 in Example 1 of the present invention.

[0021] Fig.10 This is the reproducibility of the Cu / NH2-HKUST-1@TiO2 photocatalytic CO2 reduction in Example 1 of the present invention.

[0022] Fig.11 It is the abstract figure of the present invention, which mainly shows the design concept and application of the present invention. DETAILED DESCRIPTION

[0023] The following further describes the content of the present invention, but it should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, modifications or substitutions made to the method, steps or conditions of the present invention all belong to the scope of the present invention.

[0024] Flexible TiO2 nanofiber film was prepared by electrospinning technology. MOFs were controllably grown in situ on the TiO2 surface by layer-by-layer growth (LBL) method. A series of MOFs@TiO2 composite materials with core-sheath structure were controllably prepared by modifying LBL precursor and LBL cycle times. Amino functional ligands were substituted in the LBL process to achieve amino functionalization of MOFs sheath, improve CO2 capture capacity and increase CO yield; NH2-HKUST-1@TiO2 was modified by Cu nanoparticle deposition, further providing photogenerated electron traps and carbon-carbon coupling sites, realizing the conversion of reduction products from CO to C2H5OH.

[0025] The specific synthesis process is as follows:

[0026] 1. Synthesis of flexible TiO2 nanofibers

[0027] Tetraisopropyl titanate (TIP, 1-3 g), polyvinyl pyrrolidone (PVP, 0.1-0.5 g) and acetic acid (1-5 mL) were stirred in 5-9 mL of ethanol for 1-5 hours to obtain an electrospinning precursor. The wire voltage was set to 14-16 kV and the feed rate was 2-3 mL / h. -1 The TiO2 precursor is prepared by spinning, and the TiO2 nanofiber film is obtained by calcining at 500-600°C for 1-3h.

[0028] 2. Preparation of flexible TiO2 nanofibers pre-embedded with Cu

[0029] Copper acetate (0.009-0.38 g), TIP (1-3 g), PVP (0.1-0.5 g) and acetic acid (1-5 mL) were stirred in 5-9 mL of ethanol for 1-5 h to obtain the electrospinning precursor. The wire voltage was set to 14-16 kV and the feed rate was 2-3 mL h -1 The spinning is carried out, and the product is calcined at 500-600° C. for 1-3 h to obtain a TiO2 nanofiber film pre-embedded with Cu.

[0030] 3. Preparation of core-sheath HKUST-1@nanofiber TiO2 composite photocatalyst

[0031] The core-sheath heterostructure was prepared by LBL method. A single LBL cycle process is that the Cu-embedded TiO2 is immersed in a DMF / EtOH / H2O (1:1:1) mixed solution of trimesic acid for 5-60min, the solution concentration is 0.02-0.05M, and the solution temperature is 15-120℃; after the immersion, it is transferred to a DMF / EtOH / H2O (1:1:1) mixed solution of copper acetate with a concentration of 0.03-0.06M. LBL cycles 5-50 times to achieve the in-situ growth of MOFs on the TiO2 surface. The sample is washed with ethanol and dried at 60℃ for 12 hours to obtain the core-sheath type HKUST-1@nanofiber TiO2 composite photocatalyst.

[0032] 4. Preparation of core-sheath type NH2-HKUST-1@nanofiber TiO2 composite photocatalyst

[0033] Cu-encapsulated TiO2 was immersed in a DMF / EtOH / H2O (1:1:1) mixed solution of trimesic acid and 5-aminoisophthalic acid for 5-60 min, the molar ratio of trimesic acid to 5-aminoisophthalic acid was 20:1-1:1, the total concentration of the solution was 0.02-0.05M, and the solution temperature was 15-120℃; after the immersion, it was transferred to a DMF / EtOH / H2O (1:1:1) mixed solution of copper acetate (0.03-0.06M) with a concentration of 0.03-0.06M. LBL was cycled 5-50 times to achieve the in-situ growth of MOFs on the TiO2 surface, and the core-sheath type NH2-HKUST-1@ nanofiber TiO2 composite photocatalyst was obtained after washing with ethanol and drying at 60℃ for 12 hours.

[0034] 5. Preparation of core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst

[0035] Cu nanoparticles (NPs) were introduced by photoreduction. First, 0.05 g NH2-HKUST-1@TiO2 was pre-activated in a vacuum at 100 °C for 12 hours, and then soaked in a 0.5-2.5 M copper acetate (0.5-2.5 mM) ethanol solution at room temperature for 0.5-6 hours. Then, it was irradiated with a 150-500 W xenon lamp or mercury lamp in a mixed solution of H2O / EtOH (4:1) for 0.5-5 hours, filtered and dried to obtain a core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst.

[0036] 6. CO2 reduction performance test of photocatalyst

[0037] 30 mg of freshly prepared photocatalyst was evenly dispersed on the inner wall of a 50 mL quartz tube and then purged with humidified CO2 gas for 30 min (50 mL min -1 ) to completely exclude air. Afterwards, the reactor was irradiated with a 300W Xe lamp equipped with a visible light cutoff filter (λ>400nm) at room temperature for 6h, and 1mL of the product was extracted from the reactor at intervals of 1h and analyzed by a gas chromatograph equipped with FID and TCD detectors.

[0038] The synthesized MOFs@TiO2 composite photocatalyst was subjected to XRD powder diffraction, scanning electron microscopy, transmission electron microscopy, XPS, CO2 adsorption and photocatalytic CO2 reduction tests. The results are as follows:

[0039] Figure 1 For the comparison of XRD patterns of the samples, the test results show that the MOFs@TiO2 composite photocatalyst simultaneously presents typical diffraction spectra of MOF and TiO2, indicating the successful preparation of the composite material.

[0040] Figure 2 Scanning electron microscopy images show that HKUST-1 crystals are tightly wrapped on the surface of TiO2 nanofibers to form a core-sheath heterostructure. The materials modified with amino and Cu nanoparticles show a similar core-sheath structure.

[0041] Figure 3 The transmission electron microscope image shown shows a core-sheath structure with TiO2 as the main core and MOFs as the sheath shell.

[0042] Figure 4 The XPS spectrum shown shows that the Cu 2p 3 / 2 A new peak appeared at 933.0 eV, which was attributed to Cu 0 / Cu + The binding energy peak of 918.7 eV in the Cu LMM Auger spectrum indicates that the deposited Cu nanoparticles are Cu 0In the XPS spectrum of N1s, the peak with a binding energy of 398.8 eV indicates that the deposited Cu nanoparticles are fixed in the pores of MOFs through the Cu-N interaction.

[0043] Figure 5 The CO2 adsorption-desorption isotherms shown in Figure 2 indicate that the formation of a core-sheath structure can increase the CO2 adsorption capacity to 24.1 cc g -1 Amino functionalization can further increase the adsorption capacity of NH2-HKUST-1@TiO2 to 36.1 cc g -1 , demonstrating the role of -NH2 in enhancing CO2 capture. CuNPs deposition had little effect on CO2 adsorption, indicating that Cu / NH2-HKUST-1@TiO2 retained a high CO2 affinity.

[0044] MOFs@TiO2 photocatalytic CO2 reduction performance test. 30 mg of freshly prepared photocatalyst was evenly dispersed on the inner wall of a 50 mL quartz tube, and then purged with humidified CO2 gas for 30 min (50 mL min -1 ) to completely exclude air. The reactor was irradiated with a 300W Xe lamp equipped with a visible light cutoff filter (λ>400nm) at room temperature for 6h, and 1mL of product was extracted from the reactor at every 1h interval and analyzed by a gas chromatograph equipped with FID and TCD detectors.

[0045] The test results of photocatalytic CO2 reduction performance are as follows:

[0046] like Figure 6 As shown in Figure 2, after the core-sheath structure is formed, the photocatalytic activity of the material is significantly improved, and the CO yield of HKUST-1@TiO2 reaches 8.76±0.84μmol g -1 h -1 The selectivity is 91.7%, and the CO yield of NH2-HKUST-1@TiO2 can be further improved to 43.46±0.86μmol g -1 h -1 , with a selectivity of 98.3%.

[0047] Figure 7 As shown in Figure 2, Cu / NH2-HKUST-1@TiO2 has a specific CO2 reduction efficiency to produce C2H5OH with a yield of 1.29±0.05μmol g -1 h -1 , and the selectivity was 94.2%, indicating the successful regulation of photocatalytic activity and selectivity.

[0048] Figure 8-10Reproducible studies have shown that the catalytic activity of all prepared core-sheath MOFs@TiO2 nanofibrous composite photocatalysts has excellent long-term stability.

[0049] Example 1

[0050] 1. Synthesis of flexible TiO2 nanofibers

[0051] Tetraisopropyl titanate (TIP, 1 g), polyvinyl pyrrolidone (PVP, 0.1 g) and acetic acid (1 mL) were stirred in 5 mL of ethanol for 1 h to obtain a clear, transparent, light yellow solution. Afterwards, the solution was transferred to an electrospinning device at a voltage of 14 kV and the solution feed rate was 2 mL h -1 The collected TiO2 precursor was heated in air at 2℃min -1 The heating rate was set to 500℃ and calcined for 3h. After cooling to room temperature, flexible TiO2 nanofibers were obtained.

[0052] 2. Preparation of core-sheath HKUST-1@nanofiber TiO2 composite photocatalyst

[0053] Cu-embedded TiO2 nanofibers were prepared by the same procedure as undoped TiO2 nanofibers using copper acetate (0.009 g), TIP (1 g), PVP (0.1 g), and acetic acid (1 mL) as starting materials.

[0054] The core-sheath heterostructure was prepared by LBL method. A single LBL cycle process was that the Cu-embedded TiO2 was immersed in a DMF / EtOH / H2O (1:1:1) mixed solution of trimesic acid for 60 minutes, the solution concentration was 0.02M, and the solution temperature was 15℃; after the immersion, it was transferred to a DMF / EtOH / H2O (1:1:1) mixed solution of copper acetate with a concentration of 0.03M. LBL cycle was repeated 5 times to achieve the in-situ growth of MOFs on the TiO2 surface. The sample was washed with ethanol and dried at 60℃ for 12 hours to obtain the core-sheath type HKUST-1@nanofiber TiO2 composite photocatalyst.

[0055] 3. Preparation of core-sheath type NH2-HKUST-1@nanofiber TiO2 composite photocatalyst

[0056] The amino-modified NH2-HKUST-1@TiO2 was prepared by the same procedure as HKUST-1@TiO2 using a mixed solution of trimesic acid and 5-aminoisophthalic acid (molar ratio 20:1) in DMF / EtOH / H2O (1:1:1) as the precursor.

[0057] Cu-encapsulated TiO2 was immersed in a DMF / EtOH / H2O (1:1:1) mixed solution of trimesic acid and 5-aminoisophthalic acid (molar ratio 20:1) for 60 minutes, with a total solution concentration of 0.02M and a solution temperature of 15°C; after immersion, it was transferred to a DMF / EtOH / H2O (1:1:1) mixed solution of copper acetate with a concentration of 0.03M. LBL cycles were repeated 5 times to achieve in-situ growth of MOFs on the TiO2 surface. The sample was washed with ethanol and dried at 60°C for 12 hours to obtain a core-sheath type NH2-HKUST-1@ nanofiber TiO2 composite photocatalyst.

[0058] 4. Preparation of core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst

[0059] Cu nanoparticles (NPs) were introduced by photoreduction. First, 0.05 g NH2-HKUST-1@TiO2 was pre-activated in a vacuum at 100 °C for 12 h and immersed in an ethanol solution of copper acetate (0.5 mM) for 6 h. After that, the sample was separated by filtration, dispersed in a mixed solution of H2O / EtOH (4:1), and irradiated with a 150 W mercury lamp for 5 h. After filtration and drying, the core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst was obtained.

[0060] 5. CO2 reduction performance test of photocatalyst

[0061] 30 mg of freshly prepared photocatalyst was evenly dispersed on the inner wall of a 50 mL quartz tube and then purged with humidified CO2 gas for 30 min (50 mL min -1 ) to completely exclude air. Afterwards, the reactor was irradiated with a 300W Xe lamp equipped with a visible light cutoff filter (λ>400nm) at room temperature for 6h, and 1mL of the product was extracted from the reactor at intervals of 1h and analyzed by a gas chromatograph equipped with FID and TCD detectors.

[0062] Example 2

[0063] 1. Synthesis of flexible TiO2 nanofibers

[0064] TIP (2 g), PVP (0.4 g) and acetic acid (3 mL) were stirred in 7 mL of ethanol for 2 h to obtain the electrospinning precursor. The wire voltage was set to 15 kV and the feed rate was 2.5 mL h -1 The spinning was carried out, and the product was calcined at 550°C for 2h to obtain flexible TiO2 nanofibers.

[0065] 2. Preparation of core-sheath HKUST-1@nanofiber TiO2 composite photocatalyst

[0066] Cu-embedded TiO2 nanofibers were prepared by the same procedure as undoped TiO2 nanofibers using copper acetate (0.02 g), TIP (2 g), PVP (0.4 g) and acetic acid (3 mL) as starting materials.

[0067] The core-sheath heterostructure was prepared by LBL method. A single LBL cycle process was that the Cu-embedded TiO2 was immersed in a DMF / EtOH / H2O (1:1:1) mixed solution of trimesic acid for 15 minutes, the solution concentration was 0.03M, and the solution temperature was 80℃; after the immersion, it was transferred to a DMF / EtOH / H2O (1:1:1) mixed solution of copper acetate with a concentration of 0.05M. The LBL cycle was repeated 20 times to achieve the in-situ growth of MOFs on the TiO2 surface. The sample was washed with ethanol and dried at 60℃ for 12 hours to obtain the core-sheath type HKUST-1@nanofiber TiO2 composite photocatalyst.

[0068] 3. Preparation of core-sheath type NH2-HKUST-1@nanofiber TiO2 composite photocatalyst

[0069] Cu-embedded TiO2 was immersed in a DMF / EtOH / H2O (1:1:1) mixed solution of trimesic acid and 5-aminoisophthalic acid (molar ratio 5:1) for 15 minutes, with a total solution concentration of 0.03M and a solution temperature of 80°C; after the immersion, it was transferred to a DMF / EtOH / H2O (1:1:1) mixed solution of copper acetate with a concentration of 0.05M. LBL cycles were repeated 20 times to achieve the in-situ growth of MOFs on the TiO2 surface. The sample was washed with ethanol and dried at 60°C for 12 hours to obtain a core-sheath type NH2-HKUST-1@ nanofiber TiO2 composite photocatalyst.

[0070] 4. Preparation of core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst

[0071] Cu nanoparticles were introduced by photoreduction. First, 0.05 g NH2-HKUST-1@TiO2 was pre-activated in a vacuum at 100 °C for 12 h and immersed in an ethanol solution of copper acetate (1 mM) for 3 h. Afterwards, the sample was separated by filtration, dispersed in a mixed solution of H2O / EtOH (4:1), and irradiated with a 300 W mercury lamp for 2 h. After filtration and drying, the core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst was obtained.

[0072] 5. CO2 reduction performance test of photocatalyst

[0073] 30 mg of freshly prepared photocatalyst was evenly dispersed on the inner wall of a 50 mL quartz tube and then purged with humidified CO2 gas for 30 min (50 mL min -1 ) to completely exclude air. Afterwards, the reactor was irradiated with a 300W Xe lamp equipped with a visible light cutoff filter (λ>400nm) at room temperature for 6h, and 1mL of the product was extracted from the reactor at intervals of 1h and analyzed by a gas chromatograph equipped with FID and TCD detectors.

[0074] Example 3

[0075] 1. Synthesis of flexible TiO2 nanofibers

[0076] Tetraisopropyl titanate (TIP, 3 g), polyvinyl pyrrolidone (PVP, 0.5 g) and acetic acid (5 mL) were stirred in 9 mL of ethanol for 5 h to obtain a clear, transparent light yellow solution. Afterwards, the solution was transferred to an electrospinning device with a voltage of 16 kV and a solution feed rate of 3 mL h -1 The collected TiO2 precursor was heated in air at 2℃min -1 The heating rate was set to 600℃ and calcined for 1h. After cooling to room temperature, flexible TiO2 nanofibers were obtained.

[0077] 2. Preparation of core-sheath HKUST-1@nanofiber TiO2 composite photocatalyst

[0078] Cu-embedded TiO2 nanofibers were prepared by the same procedure as undoped TiO2 nanofibers using copper acetate (0.38 g), TIP (3 g), PVP (0.5 g), and acetic acid (5 mL) as starting materials.

[0079] The core-sheath heterostructure was prepared by LBL method. A single LBL cycle process was that the Cu-embedded TiO2 was immersed in a DMF / EtOH / H2O (1:1:1) mixed solution of trimesic acid for 5 min, the solution concentration was 0.05 M, and the solution temperature was 120℃; after the immersion, it was transferred to a DMF / EtOH / H2O (1:1:1) mixed solution of copper acetate with a concentration of 0.06 M. LBL cycle was repeated 50 times to achieve the in-situ growth of MOFs on the TiO2 surface. The sample was washed with ethanol and dried at 60℃ for 12 hours to obtain the core-sheath type HKUST-1@nanofiber TiO2 composite photocatalyst.

[0080] 3. Preparation of core-sheath type NH2-HKUST-1@nanofiber TiO2 composite photocatalyst

[0081] Cu-embedded TiO2 was immersed in a DMF / EtOH / H2O (1:1:1) mixed solution of trimesic acid and 5-aminoisophthalic acid (molar ratio 1:1) for 5 minutes, with a total solution concentration of 0.05M and a solution temperature of 120℃; after immersion, it was transferred to a DMF / EtOH / H2O (1:1:1) mixed solution of copper acetate with a concentration of 0.06M. LBL cycle was repeated 50 times to achieve the in-situ growth of MOFs on the TiO2 surface. The sample was washed with ethanol and dried at 60℃ for 12 hours to obtain a core-sheath type NH2-HKUST-1@ nanofiber TiO2 composite photocatalyst.

[0082] 4. Preparation of core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst

[0083] Cu nanoparticles were introduced by photoreduction. First, 0.05 g NH2-HKUST-1@TiO2 was pre-activated in a vacuum at 100 °C for 12 h and immersed in an ethanol solution of copper acetate (2.5 mM) for 0.5 h. After that, the sample was separated by filtration, dispersed in a mixed solution of H2O / EtOH (4:1), and irradiated with a 500 W mercury lamp for 0.5 h. After filtration and drying, the core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst was obtained.

[0084] 5. CO2 reduction performance test of photocatalyst

[0085] 30 mg of freshly prepared photocatalyst was evenly dispersed on the inner wall of a 50 mL quartz tube and then purged with humidified CO2 gas for 30 min (50 mL min -1 ) to completely exclude air. Afterwards, the reactor was irradiated with a 300W Xe lamp equipped with a visible light cutoff filter (λ>400nm) at room temperature for 6h, and 1mL of the product was extracted from the reactor at intervals of 1h and analyzed by a gas chromatograph equipped with FID and TCD detectors.

[0086] Depend on Figure 6 It can be seen that amino functionalization modification of MOFs improves the affinity of the composite material to CO2, thereby improving the efficiency of CO2 reduction to produce CO. Figure 7It can be seen that the core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst of the present invention successfully achieved efficient and selective conversion of photocatalytic CO2 reduction to C2H5OH. By introducing Cu nanoparticles as CC coupling sites, the CO2 reduction product can be effectively converted into ethanol. Compared with traditional photocatalysts, Cu / NH2-HKUST-1@TiO2 exhibits higher photocatalytic activity and selectivity, achieving efficient conversion of CO2 and recycling of resources. In addition, the results of reproducible research show that ( Fig.10 ), the catalytic activity of Cu / NH2-HKUST-1@TiO2 has good stability and sustainability. This invention provides new ideas and directions for the further development of the field of photocatalytic CO2 reduction.

[0087] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A core-sheath type MOFs@TiO2 nanofibrous composite photocatalyst, characterized in that: The composite catalyst has a core-sheath structure, with flexible TiO2 nanofibers as the core and metal-organic framework materials (MOFs) as the sheath. The core and sheath are connected by coordination bonds, and the MOFs sheath layers are modified by amino functionalization and Cu nanoparticle deposition, respectively.

2. The method for preparing the core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst according to claim 1, characterized in that: The TiO2 fiber pre-embedded with Cu was used as the core, and the Cu-based MOF material HKUST-1 grown by the in situ LBL method was used as the sheath. HKUST-1 was further amino-functionalized and modified by Cu nanoparticle deposition.

3. The TiO2 fiber pre-embedded with Cu according to claim 2, characterized in that: Copper salt is added during the electrospinning process to synthesize TiO2 fibers, and the copper salt is further copper acetate.

4. The Cu-based MOFs according to claim 2 are characterized in that: The organic ligand is trimesic acid or a mixture of trimesic acid and 5-aminoisophthalic acid.

5. The preparation method according to claim 4, characterized in that: The molar ratio of trimesic acid to 5-aminoisophthalic acid is 20:1 to 1:

1.

6. The preparation method according to claim 2, characterized in that: The metal salt used in the LBL process is copper acetate, and the solvent consists of ethanol, water, and N,N-dimethylformamide in a volume ratio of 1:1:

1.

7. The preparation method according to claim 2, characterized in that: The temperature of the LBL process is 15-120°C, each cycle lasts 5-60 min, and the number of cycles is 5-50.

8. The preparation method according to claim 2, characterized in that: Cu nanoparticle deposition uses copper acetate as a precursor, the immersion time is 0.5-6h, and the light source is a 150-500W xenon lamp or mercury lamp.

9. Use of the core-sheath type HKUST-1@nanofiber TiO2 composite photocatalyst according to claim 1 in the preparation of CO by photoreduction of carbon dioxide.

10. Use of the core-sheath type NH2-HKUST-1@nanofiber TiO2 composite photocatalyst according to claim 1 in the preparation of CO by photoreduction of carbon dioxide.

11. Use of the core-sheath type Cu / NH2-HKUST-1@nanofiber TiO2 composite photocatalyst according to claim 1 in the preparation of C2H5OH by photoreduction of carbon dioxide.